INTERVENSI PARENTING EDUCATION UNTUK MENURUNKAN RISIKO STUNTING DAN WASTING: PENDEKATAN POLA ASUH HOLISTIK - Yanita Trisetyaningsih; Tri Sunarsih (LPPM STIKes BHAKTI HUSADA CIKARANG, 2026)
Stunting and wasting are major nutritional problems in toddlers that impact their growth and development, necessitating community-based educational interventions. Integrated service post (Posyandu) cadres, particularly those for toddlers, have a strategic role as health education agents, but limited knowledge poses a challenge in prevention efforts. This study aims to analyze the influence of parenting education on increasing the knowledge of integrated health post (Posyandu) cadres regarding the prevention of stunting and wasting through a holistic parenting approach.. This study used a quantitative pre-experimental design with a one-group pretest–posttest design approach. The sample in this study was 78 Posyandu cadres using a total sampling technique. The instrument used in this study was a knowledge questionnaire that had been tested for validity and reliability. Data analysis was carried out descriptively and inferentially using the Shapiro–Wilk test and paired sample t-test. The results showed an increase in the average knowledge score from 54.8 to 94.2 with a difference of 39.4 points (p < 0.001), indicating a significant difference before and after the intervention. Thus, parenting education interventions showed effective results in improving the knowledge of integrated health post (Posyandu) cadres. In conclusion, empowering cadres through holistic parenting-based education can be an effective strategy in supporting the prevention of stunting and wasting sustainably at the community level. Recommendation: Parenting education programs based on holistic parenting need to be implemented sustainably and integratedly through the empowerment of integrated health post (Posyandu) cadres to improve efforts to prevent stunting and wasting at the community level.